2022
DOI: 10.3389/fnagi.2021.706928
|View full text |Cite
|
Sign up to set email alerts
|

High Estimated Glomerular Filtration Rate Is Associated With Worse Cognitive Performance in the Hypertensive Population: Results From the China H-Type Hypertension Registry Study

Abstract: BackgroundIncreasing studies have focused on the predictive value of high estimated glomerular filtration rate (eGFR) on cardiovascular diseases and mortality; however, the association between high eGFR with cognitive function is still not established. Thus, this study aimed to determine the co-relationship between high eGFR and cognitive performance in the hypertensive population.MethodsWe conducted a baseline cross-sectional study using data from the China H-type Hypertension Registry study. Mini-Mental Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…We also found that eGFR above 105 ml/min/1.73m 2 was associated with an increased risk of dementia, a finding consistent with the results from the SCREAM project [ 6 ]. Similar U-shape relationships have been observed with other health outcomes, including total mortality [ 45 ], cardiovascular mortality [ 45 ], coronary artery calcification [ 46 ], and cognitive function [ 47 ]. Upon further interrogation, we found that an eGFR ≥ 105 ml/min/1.73m 2 was associated with more than double the risk of dementia within five years of follow-up, but was not associated after ten years of follow-up.…”
Section: Discussionsupporting
confidence: 62%
“…We also found that eGFR above 105 ml/min/1.73m 2 was associated with an increased risk of dementia, a finding consistent with the results from the SCREAM project [ 6 ]. Similar U-shape relationships have been observed with other health outcomes, including total mortality [ 45 ], cardiovascular mortality [ 45 ], coronary artery calcification [ 46 ], and cognitive function [ 47 ]. Upon further interrogation, we found that an eGFR ≥ 105 ml/min/1.73m 2 was associated with more than double the risk of dementia within five years of follow-up, but was not associated after ten years of follow-up.…”
Section: Discussionsupporting
confidence: 62%
“…Conversely, in males within this eGFR range, only glycohemoglobin demonstrated a significant increase, whereas AAC, body mass index, waist circumference, arm circumference, apolipoprotein B, total cholesterol, and triglyceride showed a decreasing pattern. Accordingly, it's postulated that the increased eGFR associating with elevated AAC in females could be primarily connected to obesity, high blood lipids or diabetes, rather than the overestimation of eGFR due to malnutrition-induced muscle loss as proposed in other literature ( 21 , 23 25 ). The trend of increased AAC scores in females at higher eGFR impacts the nonlinear relationship between eGFR and AAC in the overall population.…”
Section: Discussionmentioning
confidence: 95%
“…Creatinine clearance, used as an index of GFR, has shown that elevated GFR may be an indicator of early target organ damage [50 ▪ ]. Studies in potential kidney donors compared mGFR by iothalamate clearance and eGFR calculated by CKD-EPI equation, while measuring kidney volume by CT, and nephron number and glomerular volume according to kidney biopsy.…”
Section: Introductionmentioning
confidence: 99%